The Impact of Entrepreneurial Orientation and Halal Orientation toward Organizational Performance of Micro-Sized Enterprises - Ezanee Mohd Elias; Mohd Nasrun Mohd Nawi; Mohd Affendi Ahmad Pozin; Mazri Yaakob; Md Fauzi Ahmad; Norlila Mahidin (International Journal of Supply Chain Management, 2019)
This study investigates the impact of entrepreneurial orientation and halal orientation towards organizational performance among the micro-sized of food and beverages enterprises. Past literature showed a lesser amount of involvement of these enterprises that have been investigated so far towards their organizational performance. Therefore, this study aims to introduce and provide coverage related to entrepreneurial orientation and halal orientation among micro-sized enterprises. This study applies a quantitative method with a cross-sectional survey among the owners of the micro-sized enterprises located in the northern area of Kedah. Collection of data was done through a survey questionnaire via simple random sampling technique. The data were processed with SPSS (v.23). The results of reliability test and multiple regression analysis have shown that entrepreneurial orientation and halal orientation are indeed dissimilar in their effects on organization performance, but at the same time, they are connected to each other. It can be summarized that both of entrepreneurial orientation and halal orientation are important business strategies, but need to be investigated further. Since this is a pioneer study, more empirical works need to be done to clarify and generalize the population of micro-sized enterprises involve in halal F&B businesses in other states in Malaysia.